THE IMPACT OF THE INFORMATIZATION PROCESS ON THE DEVELOPMENT OF SOCIETY - Israilov Davronbek; Hajiyeva Zulkhumor (Research Focus International Scientific Journal, 2024)
in this article, one of the pressing problems of today is thinking about such issues as the behavior of people in the information society and the formation of skills to be able to properly use information in this process.